Rates of and reasons for condemnation of poultry carcases: harmonised methodology at the slaughterhouse. (27th May 2017) - Salines, M.; Allain, V.; Roul, H.; Magras, C.; Le Bouquin, S.
Abstract : European hygiene regulations require the condemnation of any unsafe food. However, there is little information identifying and quantifying condemnation of poultry carcases at slaughterhouses. We present an in‐depth view of rates of and reasons for the condemnation of broiler, turkey, meat and force‐feeding duck, guinea fowl carcases in France. The experiment was conducted in 10 slaughterhouses. For one year, all condemnations were recorded on a standard form following a national reference system. The rates of and reasons for condemnation, as well as factors influencing variation were investigated. The global condemnation rates were 1.04 per cent for broilers, 1.85 per cent for turkeys, 1.23 per cent for meat ducks, 1.42 per cent for force‐feeding ducks and 1.20 per cent for guinea fowl. Condemnation rates depended on several factors including slaughterhouse, animal gender and season. Reasons for condemnation varied with species, for example, the three main reasons for broilers were cachexia (41.8 per cent of condemned batches), generalised congestion (29.3 per cent) and non‐purulent cutaneous lesions (14.2 per cent) versus conformation abnormalities (58.6 per cent), cachexia (14.61 per cent) and ascites (14.56 per cent) for meat ducks. While the condemnation rates can be considered low for all species, the difference between the rates of and reasons for condemnation highlights the need to lead species‐specific epidemiological studies to improve the sanitary situation of poultry production.